Konstruksi Etika Kristen Berbasis Teologi Salib: Analisis Eksegetis Roma 7:14 dalam Kehidupan Orang Kristen - Djoko Sukono; Daniel Pesah Purwonugroho (Sekolah Tinggi Teologi Nusantara, 2026)
This paper aims to construct Christian ethics based on the theology of the cross through an exegetical analysis of Romans 7:14. Romans 7:14 frames humanity's inability to respond to ethical demands due to its condition of being sold under the power of sin. The power of sin shackles humanity. This condition makes it impossible for humanity to produce an ethical life that originates from within itself. On the one hand, the theology of the cross affirms God's role through the cross of Christ, which transforms humanity. The theology of the cross frames God's grace in the cross of Christ to save humanity. This combination brings a constructive approach to forming a polarized Christian ethic. Christian ethics are often polarized through a normative-legalistic or spiritual-experiential approach. An integrative approach based on God's grace amid human inability is needed. Through a descriptive qualitative approach, the exegetical analysis of Romans 7:14 reveals a basic need of humanity, namely freedom from the bondage of sin that shackles human efforts. This freedom brings humanity to God's grace, which enables humanity to live an ethical life. This paper offers an analysis of Romans 7:14 with the theology of the cross paradigm as its ethical foundation. This paper also constructs a Christian ethic rooted in human powerlessness and complete dependence on God's grace.AbstrakRoma 7:14 membingkai ketidakmampuan manusia dalam merespon tuntutan etis karena kondisi keterjualan di bawah kuasa dosa. Kuasa dosa membelenggu umat manusia. Teologi salib membingkai anugerah Allah di dalam salib Kristus untuk menyelamatkan umat manusia. Kombinasi ini membawa pendekatan konstruktif untuk membentuk etika Kristen yang terpolarisasi. Etika Kristen seringkali terpolarisasi melalui pendekatan normatif-legalistik ataupun spiritual-eksperiensial. Dibutuhkan sebuah pendekatan integratif yang beraraskan anugerah Allah di tengah ketidakmampuan manusia. Tulisan ini bertujuan untuk menkonstruksi etika Kristen berbasis teologi salib melalui analisis eksegetis Roma 7:14. Melalui pendekatan kualitatif deskriptif, analisis eksegetis Roma 7:14 memaparkan sebuah kebutuhan mendasar umat manusia yaitu kebebasan dari belenggu dosa yang membelenggu upaya diri manusia. Kebebasan tersebut membawa manusia kepada anugerah Allah yang memampukan umat manusia menjalankan kehidupan etisnya. Tulisan ini menawarkan analisis Roma 7:14 dengan paradigman teologi salib sebagai fondasi etiksa. Tulisan ini juga mengkonstruksi etika Kristen yang berakar pada ketidakberdayaan manusia dan kebergantungan penuh pada anugerah Allah. Kata Kunci : Etika Kristen, Teologi Salib, Eksegetis, Roma 7:14